The Analysis of Form, Functions and Code Switching Factors in the Film Kehormatan di Balik Kerudung - Ifa Lathifah; Agus Sariono; Ali Badruddin (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2023)
Code-switching is the alteration or shift in the usage of one language to another within the context of communication, often occurring spontaneously and naturally. This study aims to find code switching forms, its underlying factors, as well as its function found in the Kehormatan di Balik Kerudung. The data of this research are players’ utterances in which code switching appear. The data collected were analyzed using Poplack’s theory (1980) to determine the form of code switching, Grosjean’s theory (2010) to find the functions of code switching, and Azhar’s, et al (2011) to find the factors behind the code switching. The results of this study indicate that extrasentential code-switching in the form of Javanese particles highly dominates the code-switching practices compared to the other two, namely intrasentential and intersentential, namely there were 30 extrasentential code-switching, 22 intrasentential and 7 intersentential. Some of the code-switching functions, are among others: to start a conversation, to confirm the conversation, to end the conversation, to confirm or emphasize statements, to ask for approval, and to answer doubts. Six factors underlying the code switching were among others: speakers, speech partners, topics of conversation, place and time of speech events, functions and objectives, as well as variety and level of speech.